What's next? : unconventional wisdom on the future of the world economy - Hale, David; Hale, Lyric (Yale University Press, 2011)
The world spins in economic turmoil, and who can tell what will happen next? Cold numbers and simple statistical projections don't take into account social, financial, or political factors that can dramatically alter the economic course of a nation or a region. In this unique book, more than twenty leading economists and experts render thorough, rigorously researched prognoses for the world's major economies over the next five years. Factoring in such varied issues as the price of oil, the strength of the U.S. dollar, geopolitics, tax policies, and new developments in investment decision making, the contributors ground their predictions in the realities of current events, political conditions, and the health of financial institutions in each national economy. The most comprehensive volume on the global economy available today, this book presents up-to-date research on Russia, Australia, Europe, sub-Saharan and South Africa, the major Asian economies, North America, and the largest economies of Latin America. With unsurpassed expertise, the authors explain what's going on in individual countries, how important current global issues will impact them, and what economic scenarios they most likely will face in upcoming years.